Multi-layer faults in the architectures of mobile, context-aware adaptive applications: a position paper - Sama, Michele; Rosenblum, David S; Wang, Zhimin; Elbaum, Sebastian (International Conference on Software Engineering 2008, 2008)
Five cellphones are sold every second, and there are four times more cellphones than computers, meaning there are some billions of mobile handheld devices in existence. Modern cellphones are equipped with multiple context sensors used by increasingly sophisticated software applications that exploit the sensors, allowing the applications to adapt automatically to changes in the surrounding environment, such as by responding to the location and speed of the user. The architecture of such applications is typically layered and incorporates a context-awareness middleware to support processing of context values. While this layered architecture is very natural for the design and implementation of applications, it gives rise to new kinds of faults and faulty behavior modes, which are difficult to detect using existing validation techniques. In this paper we provide scenarios illustrating such faults and exploring how they manifest in context-aware adaptive applications.